Wewenang dan Peran Wilayah Hisbah dalam Pengawasan Pasar dan Ekonomi dalam Perspektif Fiqih Siyasah - Fauzan Abdullah, Ahmad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2018)
This paper is a literature research using content analysis in reviewing function of al hisbah institution according fiqih siyasah in market and economic activity. The idea and practice of al hisbah have been knowns scince the days of propert Muhammad (P.B,U,H). It was concerned with commanding righteuousness and prohibiting evil .during this period This al hisbah was assigned to see the every day about practices of markets in which wrong doing associated with trading practices often occured . al hisbah as institution must be obligation of all muslim leader to appoint person and give this person necessary authorithy and power to carry out of duty,preventing illegal practices,warn and educate perpetrators with the available provision for the sake of public interests. The conclusion in this study states that hisbah has a function as an evaluator of economic and market activities and that ensure its run in accordance with Islamic Shari'a. Such as prohibiting the illegal transaction in markets, illegal economic activities, guarding pricing, prohibit the sale and purchase of money, and so another.